Multivariate Lesion-Behavior Mapping of General Cognitive Ability and Its Psychometric Constituents - Bowren, Mark; Adolphs, Ralph; Bruss, Joel; Manzel, Kenneth; Corbetta, Maurizio; Tranel, Daniel; Boes, Aaron D. (The Journal of neuroscience, 2020)
General cognitive ability, or general intelligence (g), is central to cognitive science, yet the processes that constitute it remain unknown, in good part because most prior work has relied on correlational methods. Large-scale behavioral and neuroanatomical data from neurologic patients with focal brain lesions can be leveraged to advance our understanding of the key mechanisms of g, as this approach allows inference on the independence of cognitive processes along with elucidation of their respective neuroanatomical substrates. We analyzed behavioral and neuroanatomical data from 402 humans (212 males; 190 females) with chronic, focal brain lesions. Structural equation models (SEMs) demonstrated a psychometric isomorphism between g and working memory in our sample (which we refer to as g/Gwm), but not between g and other cognitive abilities. Multivariate lesion-behavior mapping analyses indicated that g and working memory localize most critically to a site of converging white matter tracts deep to the left temporo-parietal junction. Tractography analyses demonstrated that the regions in the lesion-behavior map of g/Gwm were primarily associated with the arcuate fasciculus. The anatomic findings were validated in an independent cohort of acute stroke patients ( n = 101) using model-based predictions of cognitive deficits generated from the Iowa cohort lesion-behavior maps. The neuroanatomical localization of g/Gwm provided the strongest prediction of observed g in the new cohort ( r = 0.42, p < 0.001), supporting the anatomic specificity of our findings. These results provide converging behavioral and anatomic evidence that working memory is a key mechanism contributing to domain-general cognition. SIGNIFICANCE STATEMENT General cognitive ability (g) is thought to play an important role in individual differences in adaptive behavior, yet its core processes remain unknown, in large part because of difficulties in making causal inferences from correlated data. Using data from patients with focal brain damage, we demonstrate that there is a strong psychometric correspondence between g and working memory – the ability to maintain and control mental information, and that the critical neuroanatomical substrates of g and working memory include the arcuate fasciculus. This work provides converging behavioral and neuroanatomical evidence that working memory is a key mechanism contributing to domain-general cognition.